Barriers and facilitators to cancer clinical trial enrollment and participation among rural populations: a scoping review protocol. Issue 7 (1st July 2022) - Palokas, Michelle; Christian, Robin; Hinton, Elizabeth; Duhe, Roy; Thomas, Toms; Torres, Elisa; Jordan, Christina; Gordy, Xiaoshan Z.; Sharma, Manvi; Gomillia, Courtney; Stefanek, Michael; Robinson, William "Rusty"
ABSTRACT: Objective: The objective of this scoping review is to identify barriers and facilitators related to cancer clinical trial enrollment and participation among rural populations. Introduction: Advancing the effectiveness of cancer treatment and increasing early detection of cancer relies on enrollment and participation of individuals in cancer clinical trials. Lack of enrollment and participation in trials is a concern, and there is evidence that individuals living in rural areas are unlikely to participate in such trials. Information on barriers to, and facilitators of, enrollment and participation in cancer clinical trials is needed for the development of evidence-based interventions to increase the enrollment and participation of rural populations. Inclusion criteria: The review will consider studies on adults aged 18 years or older living in rural areas. Studies that report on barriers and facilitators to enrollment and participation in cancer clinical trials, including both cancer therapeutic and cancer early detection trials, will be included in the review. The review will consider quantitative, qualitative, and text and opinion papers for inclusion. Methods: The search strategy will aim to locate published primary studies, reviews, and opinion papers, the latter including those by professional oncology organizations. The databases to be searched include MEDLINE, CINAHL, Embase, Web of Science, and Cochrane Library. Gray literature databases will also be searched. Two independent reviewers will retrieve full-text studies and extract data. The results will be presented in diagrammatic format with a narrative summary.